Legalizing Bribes - Giancarlo Spagnolo; Martin Dufwenberg (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2012)
Harassment bribes - payments people give in order not to be denied what they are legally entitled to – are common in for example India. Kaushik Basu recently made a ''radical'' proposal to reduce its occurrence: Legalize the act of giving the bribe and double the fine for accepting the bribe! We develop a formal model and delineate circumstances under which Basu's proposal works well or poorly. We discuss a modified scheme where immunity is conditional on reporting that we argue addresses the main issues raised against the proposal. We highlight complementarities between these schemes and other policies aimed a improving the accountability and performance of the public sector, and of law enforcement agencies in particular. We conclude discussing the implications for the fight of more harmful forms of corruption.
Keywords: D73; K42; O17; 330; Bribes; Corruption; Governance; Immunity; Law enforcement; Leniency; Whistleblowers